2020
DOI: 10.1556/446.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Application of hyperspectral imaging to detect toxigenic Fusarium infection on cornmeal

Abstract: One of the most important food safety issues is the detection of mycotoxins, the ubiquitous, natural contaminants in cereals. Hyperspectral imaging (HSI) is a new method in food science, it can be used to predict non-destructively the changes in composition and distribution of compounds. That is why, in the last decade, the potential of HSI has been evaluated in many fields of food science, including mycotoxin research.The aim of the recent study was to test the feasibility of HSI for the differentiation accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Due to the high RMSE obtained, the authors considered HSI-NIR suitable for FDK detection in oats. On the other hand, recently published works attempted the quantification of DON using HSI but in barley or corn (Parrag et al, 2020;Su et al, 2021). However, Parrag et al (2020) predicted the level of DON in corn homogenized samples using a ROI of 20 × 100 pixels instead of single kernels.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high RMSE obtained, the authors considered HSI-NIR suitable for FDK detection in oats. On the other hand, recently published works attempted the quantification of DON using HSI but in barley or corn (Parrag et al, 2020;Su et al, 2021). However, Parrag et al (2020) predicted the level of DON in corn homogenized samples using a ROI of 20 × 100 pixels instead of single kernels.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of publications, Wang et al explored the possibilities of using NIR-HSI for the detection of AFLAs in corn kernels (Chu et al, 2017;Wang et al, 2014;. HSI is predominately used to measure intact kernels; the technique has been also utilized for the analysis of milled grain Firrao et al, 2010;Parrag et al, 2020;Zhao et al, 2020). Parrag et al reported the use of HSI to set-up models capable of either quantitative or discriminant analysis using milled samples.…”
Section: Hsi and Sknir For Mycotoxin Screening On A Single Kernel Levelmentioning
confidence: 99%
“…Corn Fungal infection, FUM, AFLA B 1 (Chu et al, 2020;Chu et al, 2017;Del Fiore et al, 2010;Firrao et al, 2010;Kandpal et al, 2015;Kimuli, Wang, Jiang, et al, 2018;Kimuli, Wang, Lawrence, et al, 2018;Lu et al, 2022;Parrag et al, 2020;Tao et al, 2020;Wang et al, 2014;Williams et al, 2010;Williams et al, 2012;Yang et al, 2020;Zhao et al, 2017;Zhu et al, 2016) Wheat Fungal infection, DON, OTA, ergosterol (Alisaac et al, 2019;Barbedo et al, 2017;Bauriegel et al, 2011;Berman et al, 2007;Dammer et al, 2011;Delwiche et al, 2010;Delwiche et al, 2019;Femenias, Bainotti, et al, 2021;Liang et al, 2020;Nadimi et al, 2021;Ropelewska & Zapotoczny, 2018;Senthilkumar et al, 2016;Shao et al, 2020;Shi et al, 2020;Singh et al, 2012;Singh et al, 2007;Zhao et al, 2020) Rice Fungal infection (Siripatrawan & Makino, 2015;Wu et al, 2020) Oats DON (Tekle et al, 2015) Peanuts Fungal contamination (He et al, 2021;Jiang et al, 2016;Qi et al, 2019;Qiao et al, 2017) Barley DON…”
Section: Target Contaminants Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, good calibration required for quantitative accurate chemical analysis requires is laborious as requires multiple analysis by standard and NIR methods simultaneously. Finally, Raman spectroscopy and hyperspectral imaging have found further food research applications, such as the screening of adulterants in cereals or as a non-destructive approach for the nutritional quality of fruits, determination of antimicrobial drugs, mycotoxins and mycotoxigenic fungi (see, for example, [236][237][238][239][240]).…”
Section: Geographical Origin Of Coffee and Honey And Coconut Water Authenticitymentioning
confidence: 99%